Antidiarrheal Effect of Fermented Millet Bran on Diarrhea Induced by Senna Leaf in Mice - Shujun Chen; Minquan Hao; Lizhen Zhang (Foods, 2022)
Bacillus natto is a kind of probiotic with various functional characteristics, which can produce a lot of nutrients during growth and reproduction. Bacillus natto was used as strain, the number of viable bacteria and the content of soluble dietary fiber in millet bran were used as indexes to study the effects of inoculum size, fermentation time, and fermentation temperature on the fermentation effect, and the optimal fermentation conditions were determined by a response surface experiment. The antidiarrhea effect of fermented millet bran prepared under the best technological conditions was evaluated. The results showed that the optimum fermentation conditions were as follows: inoculum size was 7.48%, fermentation time was 47.04 h, and fermentation temperature was 36.06 °C. Under the optimal fermentation conditions, the viable bacteria count of millet bran was 8.03 log CFU/mL and the soluble dietary fiber content was 12.14%. The fermented millet bran can significantly reduce the intestinal thrust rate and serum levels of IL-6, IL-12, and TNF-α, and significantly increase the secretion of SIgA in the intestinal mucosa, which can relieve diarrhea induced by senna leaf in mice. The results of this study can provide the scientific basis for deep processing of millet bran and efficient utilization of fermented millet bran, and also provide the theoretical basis for clinical treatment of diarrhea.